Spatial Patterns of Ectomycorrhizal Assemblages in a Monospecific Forest in Relation to Host Tree Genotype - Lang, Christa; Finkeldey, Reiner; Polle, Andrea (Frontiers in Plant Science, 2013)
Ectomycorrhizas (EcM) are important for soil exploration and thereby may shape belowground interactions of roots. We investigated the composition and spatial structures of EcM assemblages in relation to host genotype in an old-growth, monospecific beech (Fagus sylvatica) forest. We hypothesized that neighboring roots of different beech individuals are colonized by similar EcM assemblages if host genotype had no influence on the fungal colonization and that the similarity would decrease with increasing distance of the sampling points. The alternative was that the EcM species showed preferences for distinct beech genotypes resulting in intraspecific variation of EcM-host assemblages. EcM species identities, abundance and exploration type as well as the genotypes of the colonized roots were determined in each sampling unit of a 1 L soil core (r = 0.04m, depth 0.2m). The Morisita-Horn similarity indices (MHSI) based on EcM species abundance and multiple community comparisons were calculated. No pronounced variation of MHSI with increasing distances of the sampling points within a plot was found, but variations between plots. Very high similarities and no between-plot variation were found for MHSI based on EcM exploration types suggesting homogenous soil foraging in this ecosystem. The EcM community on different root genotypes in the same soil core exhibited high similarity, whereas the EcM communities on the root of the same tree genotype in different soil cores were significantly dissimilar. This finding suggests that spatial structuring of EcM assemblages occurs within the root system of an individual. This may constitute a novel, yet unknown mechanism ensuring colonization by a diverse EcM community of the roots of a given host individual.